JURA - Juristische Ausbildung (De Gruyter, 1999)
JURA is a monthly educational journal for law students. Written in an easy-to-understand and concise style, the articles provide up-to-date information at a high academic level. Includes index cards on case law, sections on elective and required subjects, refreshers, practice exams, and homework exercises.